Professional Forestry Education in India for the 21st Century - Dogra, A. S. (Indian Forester, 2013)
Forestry is being increasingly seen as an important factor in rural development. A forester must therefore recognize the need for multidisciplinary and interdisciplinary approaches to problem solving within forest management, in watersheds as well as in respect of trees outside forests. These developments require the broadening of the scope of forestry education to include socioeconomic aspects with traditional biophysical subjects. These require very different skills from those traditionally acquired by professional foresters. Regional and international partnerships of universities can make significant contribution in aligning forestry education to address economic, environmental and social objectives.